A framework for blockchain and internet of things integration in improving food security in the food supply chain - Guixia, Xiao; Samian, Normalia; Mohd Faizal, Muhammad Faiz; Mohd As’Ad, Muhammad Alif Zakwan; Mohamad Fadzil, Muhammad Firdaus; Abdullah, Azizol; Seah, Winston Khoon Guah; Ishak, Mastura; Hermadi, Irman (Semarak Ilmu Publishing, 2024)
Food security, as defined by the United Nations' Committee on World Food Security, means that “all people, at all times, have physical, social, and economic access to sufficient, safe, and nutritious food that meets their food preferences and dietary needs for an active and healthy life”. Food security is not just ensuring food sufficiency, but also ensuring the quality and the reliability of supply chains which have become more complex with diversified sources of farm productions. Some common issues in food supply chains are lacking efficient traceability of product origins and distributions. Blockchain is an emerging technology for the agricultural supply chain which could monitor food quality and safety by digitally tracking data and processes of material resources. Meanwhile, the Internet of Things (IoT) system is used for diagnosis and control in smart agriculture such as crop growth observation that can produce good quality and sustainable farm production. This work proposes a framework of the integration of blockchain with IoT to improve the reliability of food supply chain (FSC) by focusing on optimizing the consensus algorithm of blockchain. The expected outcome is to produce an efficient traceability and higher quality transactions which can integrate all procedures and dealings in real-time processes across the FSC.